PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA VIDEO TERHADAP TINGKAT PENGETAHUAN KEBERSIHAN DIRI ANAK SEKOLAH DASAR - Jesica Dwi Saputri; Titik Anggraeni; Ahmad Syamsul Bahri; Sutanta Sutanta; Sri Sayekti Heni Sunaryanti (Jurnal Cakrawala Keperawatan, 2025)
Background: Personal hygiene is an effort by an individual to maintain the health and cleanliness of the body to achieve optimal health conditions and prevent disease. At SDN Gedongrejo, no previous research has been conducted, although health counseling has been provided by the local health center. However, the students have not applied the information given. The purpose of this study is to determine the effect of health education using video media on the level of personal hygiene knowledge among elementary school children. Purpose: This study aims to understand the influence of health education using video media on the level of personal hygiene knowledge among elementary school children. Methods: This research is a quantitative study with a quasi-experimental design using a pretest-posttest design without a control group. The sampling technique used total sampling, with 72 respondents. Data were collected using a questionnaire and analyzed with the Wilcoxon Matched Pairs Test. Results: The level of knowledge among students at SDN Gedongrejo before receiving health education via video showed that 21 respondents (29.2%) had moderate knowledge, 51 respondents (70.8%) had good knowledge, and no respondents (0%) had poor knowledge. After receiving the health education on personal hygiene, all 72 respondents (100%) had good knowledge, with no respondents in the moderate or poor knowledge categories (0%). Conclusion: There is a significant effect of health education using video media on the level of personal hygiene knowledge among elementary school children at SDN Gedongrejo, with a p-value of 0.000. It is expected that all students can learn to maintain personal hygiene to prevent illness.